As políticas públicas da educação superior: a educação a distância nos governos FHC e Lula (1995-2006) - Guasti, Susana Pitol (2009)
This paper presents the differences and / or continuity of public policies in relation to distance education in Brazil, the governments of Fernando Henrique Cardoso and Luiz Inacio Lula da Silva, during the period from 1995 to 2006. It analyzes the contributions of intellectuals linked to critical theory, education policies in higher education distance in Brazil in that period and reflects the light of critical theory, its use of technology in the context of capitalist society and in particular of education. Shows by means of literature and analysis of data from the National Institute of Pedagogical Research (INEP), the Brazilian higher education and the integration of ODL in the expansion of higher education from the perspective of public policies and discourse of democratization. For this, it was necessary to understand the direction given to educational policies in the country, based on the influence of the recommendations of outside agencies such as the World Bank. The interpretation of the results of its expansion, obtained during the administrations of Fernando Henrique Cardoso and Luiz Inácio Lula da Silva, has identified that the neoliberal ideology was present in the higher education reforms, and the production of knowledge in the "knowledge society" took shape through these policies. Science policies of the 1990s consolidated the hegemony of a private educational design. The theoretical framework that gave support to the analysis made based on the ideas of the Frankfurt School. The completion of the work shows that while there is continuity in public policies in distance education for higher education in the Lula government in relation to President Fernando Henrique Cardoso. FHC sought the massification of higher education, while Lula took these policies of private education to the public as a tool of "democratization" of education, and built an evaluation process in distance education in the manner that deployed by the previous government to face teaching.